Glycolate Induces Redox Tuning Of Photosystem II in Vivo: Study of a Photorespiration Mutant. Issue 3 (23rd May 2018) - Messant, Marine; Timm, Stefan; Fantuzzi, Andrea; Weckwerth, Wolfram; Bauwe, Hermann; Rutherford, A. William; Krieger-Liszkay, Anja
Abstract : Glycolate accumulated in a photorespiration mutant replaces the bicarbonate on the acceptor-side iron of PSII, lowering the yield of singlet oxygen by redox tuning the primary quinone. Abstract: Bicarbonate removal from the nonheme iron at the acceptor side of photosystem II (PSII) was shown recently to shift the midpoint potential of the primary quinone acceptor QA to a more positive potential and lowers the yield of singlet oxygen ( 1 O2 ) production. The presence of QA − results in weaker binding of bicarbonate, suggesting a redox-based regulatory and protective mechanism where loss of bicarbonate or exchange of bicarbonate by other small carboxylic acids may protect PSII against 1 O2 in vivo under photorespiratory conditions. Here, we compared the properties of QA in the Arabidopsis ( Arabidopsis thaliana ) photorespiration mutant deficient in peroxisomal HYDROXYPYRUVATE REDUCTASE1 ( hpr1-1 ), which accumulates glycolate in leaves, with the wild type. Photosynthetic electron transport was affected in the mutant, and chlorophyll fluorescence showed slower electron transport between QA and QB in the mutant. Glycolate induced an increase in the temperature maximum of thermoluminescence emission, indicating a shift of the midpoint potential of QA to a more positive value. The yield of 1 O2 production was lowered in thylakoid membranes isolated from hpr1-1 compared with the wild type, consistent with a higher potential of QA /QA − . In addition, electron donation to photosystem I was affected in hpr1-1 at higher light intensities, consistent with diminished electron transfer out of PSII. This study indicates that replacement of bicarbonate at the nonheme iron by a small carboxylate anion occurs in plants in vivo. These findings suggested that replacement of the bicarbonate on the nonheme iron by glycolate may represent a regulatory mechanism that protects PSII against photooxidative stress under low-CO2 conditions.